Multifunctional hydrogel for promoting healing of diabetic wound and preparation method thereof
By combining Ti3C2Tx-Ag nanocomposite with peony glycoside, KC@PF@TA hydrogel was formed, and the problem of poor effect of existing diabetic wound healing materials in cell proliferation and tissue regeneration was solved, and a significant improvement in diabetes was achieved The effect of wound healing speed and quality.
Patent Information
- Application Number
- CN202411414935.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
AI Technical Summary
Existing diabetic wound healing materials have limited performance in cell proliferation and tissue regeneration, especially when Ti3C2TxMXene and AgNPs composites are used alone, they do not have obvious effects in promoting cell proliferation and tissue regeneration.
KC@PF@TA hydrogel made of Ti3C2Tx-Ag nanocomposite and paeonylanin (PF) was mixed with Ti3C2Tx-Ag nanocomposite with oxidized konjac glucomannan and carboxymethyl chitosan , form nanocomposite hydrogels, enhance their antibacterial and photothermal properties, and promote cell proliferation and tissue regeneration.
It significantly improves the healing speed and quality of diabetic wounds. KC@PF@TA hydrogel has outstanding performance in accelerating inflammatory response inhibition, angiogenesis and tissue remodeling, and has excellent antibacterial, cell proliferation and wound healing acceleration capabilities.
Smart Images

Figure HDA0005079146190000011 
Figure HDA0005079146190000021 
Figure HDA0005079146190000031
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medicine, and in particular relates to a multifunctional hydrogel for promoting healing of diabetic wounds and a preparation method thereof. Background Art
[0002] Diabetes mellitus (DM) is a chronic metabolic disorder characterized by persistent hyperglycemia, which leads to various complications, including impaired wound healing. Chronic wounds, especially diabetic ulcers, pose major clinical challenges due to their slow healing, high risk of infection, and easy recurrence. Approximately 15% of diabetic patients worldwide will develop at least one stubborn foot ulcer in their lifetime, of which approximately 20% eventually lead to lower limb amputation. In addition, the risk of wound infection in diabetic patients is four times that of non-diabetic patients, making it a global health concern. The main causes of poor wound healing in diabetic patients are angiogenesis disorders, chronic inflammation, and bacterial infection, among others. This emphasizes the need for advanced therapeutic materials designed to effectively target these problems and promote wound healing.
[0003] Recent advances in biomedical materials have led to the development of multifunctional hydrogels aimed at improving wound healing. These hydrogels are usually composed of biocompatible and biodegradable polymers with high water retention, creating a moist environment that promotes cell migration and tissue regeneration. In addition, they can also be used as drug delivery systems to control the release of antibiotics, anti-inflammatory agents, or growth factors directly to the wound surface, thereby improving drug concentration and bioavailability and accelerating healing. However, the practical application of hydrogels still faces several challenges. Conventional hydrogels often have low mechanical strength and are prone to rapid degradation in body fluids. This limitation reduces their ability to maintain drug delivery and cover large or deep wounds for a long time. In addition, controlling the drug release rate remains a problem, often resulting in initial excessive drug release followed by insufficient drug availability in later stages.
[0004] Nanocomposite hydrogels have received significant attention due to their ability to combine the structural advantages of hydrogels with the functional advantages of nanomaterials. This synergy allows the creation of materials that not only support wound architecture but also enhance drug delivery and actively modulate the local microenvironment, aiding the wound healing process. Various nanomaterials, including copper, zinc, silver, graphene oxide, and MXenes, have been incorporated into hydrogels to improve their physicochemical properties. Among them, Ti3C2Tx is a new type of 2D nanomaterial that shows promise in the treatment of diabetic wounds due to its high specific surface area, mechanical strength, photothermal, and antimicrobial properties. The large surface area of Ti3C2Tx provides a large number of active sites for the adsorption and controlled release of therapeutic drugs, making it particularly valuable in the long-term management of diabetic wounds where sustained treatment is critical.
[0005] Literature (Rasool K, Helal M, Ali A, et al. Antibacterial Activity ofTi3C2T x MXene.ACS Nano.2016;10(3):3676-3684) disclosed Ti3C2T x MXene has antibacterial activity and has a strong inhibitory effect on a variety of bacteria. However, it does not show a significant pro-proliferation effect in terms of cell proliferation and tissue regeneration. x MXene-Functionalized FibrousScaffolds with Photothermal Antibacterial Activity for Accelerating WoundHealing. Journal of Materials Chemistry B. 2020; 8(26):5712-5722.) Ti3C2T disclosed x The application of MXene materials in wound healing mainly plays an antibacterial and photothermal role. However, it was found that the effect on promoting cell proliferation was not obvious, and the proliferation level was lower than expected. x MXene-Based Nanocomposite Hydrogel with Photothermal and AntibacterialActivity for Accelerating Wound Healing. Journal of Nanobiotechnology. 2021; 19:27.) Ti3C2T disclosed x The performance of silver nanoparticle-loaded hydrogel, although the material has significant effects in antibacterial and photothermal therapy, is limited in promoting cell proliferation and tissue regeneration, and the overall pro-proliferation effect is not obvious. The literature (Xue Q, Zhang H, Zhu M, et al. A MXene-Based Antibacterial and Photothermal Nanocomposite Hydrogel Enhances Wound Healing in Diabetes. Nano Research. 2021; 14(7): 2170-2179.) discloses the application of MXene nanocomposite hydrogel in diabetic wounds, and discloses Ti3C2T xand AgNPs composites promoted wound healing via antibacterial and photothermal effects, but the promotion effect on cell proliferation was limited and not obvious.
[0006] In short, Ti3C2T x MXene and AgNPs materials have antibacterial and photothermal effects, but their direct effects on cell proliferation and tissue regeneration are not obvious, and their proliferation-promoting effects are limited when used alone. x MXene and AgNPs composites were used in the study of diabetic wounds, and it was unexpectedly found that Ti3C2T x The KC@PF@TA hydrogel made of MXene and AgNPs composites (TA) and paeoniflorin (PF) significantly enhanced cell proliferation and tissue regeneration, producing a significant synergistic effect. The experimental results showed that the KC@PF@TA group showed a better effect in wound healing, far exceeding the KC and KC@PF groups, indicating the importance of the synergistic effect of TA and PF in promoting diabetic wound repair. Summary of the invention
[0007] The purpose of the present invention is to provide a multifunctional hydrogel for promoting diabetic wound healing and a preparation method thereof.
[0008] To achieve the purpose of the present invention, the following technical solutions are provided.
[0009] In one embodiment, a hydrogel for promoting diabetic wound healing of the present invention comprises Ti3C2T x -Ag, paeoniflorin (PF) and a gel matrix comprising oxidized konjac glucomannan (OKGM) solution and carboxymethyl chitosan (CMCS).
[0010] Furthermore, the hydrogel of the present invention is prepared by the following method, which comprises:
[0011] 1) Ti3C2T x The powder was dispersed in deionized water, added to AgNO3 solution, stirred, heated to boiling, and an appropriate amount of sodium citrate solution was added. After the reaction was completed, the precipitate was separated to obtain Ti3C2T x -Ag(TA) powder;
[0012] 2) Ti3C2T x -Ag(TA) powder was dispersed in deionized water to form a dispersion and paeoniflorin (PF) was mixed with oxidized konjac glucomannan (OKGM) solution and carboxymethyl chitosan (CMCS) solution to prepare KC@PF@TA hydrogel.
[0013] In some embodiments, in the above-mentioned hydrogel, in step 2), the mass ratio of TA to PF is 1:(1-1.2), preferably 1:1.2.
[0014] In some embodiments, in the hydrogel of the present invention, in step 2), Ti3C2T x The mass ratio to Ag is 1:(1-10).
[0015] Preferably, in the above hydrogel, in step 2), Ti3C2T x The mass ratio with Ag is 1:5.
[0016] In some embodiments, the present invention provides a method for preparing a hydrogel for promoting diabetic wound healing, comprising the following steps:
[0017] 1) Ti3AlC2 powder was added to 40% HF solution, stirred and reacted at room temperature in the dark, the obtained reaction mixture was centrifuged, the supernatant was discarded, and the precipitate was washed with deionized water until the pH of the supernatant was close to neutral. The precipitate was mixed with 25% TMAOH, stirred and reacted at room temperature in the dark, centrifuged after the reaction, and the precipitate was washed with deionized water until the pH reached neutral. The precipitate was resuspended in deionized water and ultrasonically treated, the colloidal solution was separated, and vacuum freeze-dried to obtain Ti3C2T x Nano powder.
[0018] 2) Ti3C2T x The powder was dispersed in deionized water to form a uniform dispersed solution, added to the AgNO3 solution, stirred and mixed, heated to boiling, and then added with an appropriate amount of 1% sodium citrate solution to react. After the reaction was completed, it was cooled to room temperature, the precipitate was separated, washed with deionized water, and the precipitate was vacuum freeze-dried to obtain Ti3C2T x -Ag nanocomposite powder;
[0019] 3) Ti3C2T x -Ag powder was ultrasonically dispersed in deionized water to form a dispersion, paeoniflorin (PF) was added, and then mixed with oxidized konjac glucomannan (OKGM) solution and carboxymethyl chitosan (CMCS) solution to prepare OKGM / CMCS@PF@Ti3C2T x -Ag hydrogel (abbreviated as KC@PF@TA hydrogel).
[0020] In some embodiments, in the preparation method of the present invention described above: in step 1), the mass volume ratio of Ti3AlC2 to TMAOH = 1 g Ti3AlC2: 10 mL TMAOH.
[0021] In some embodiments, in the preparation method of the present invention, in step 2), Ti3C2T xThe mass ratio to Ag is 1:(1-10), preferably 1:5.
[0022] In some embodiments, in the preparation method of the present invention, in step 3), the mass ratio of OKGM to CMCS is 2:1.
[0023] In some embodiments, in the preparation method of the present invention, in step 3), the dispersed solution contains Ti3C2T x -Ag concentration 1mg / mL.
[0024] In some embodiments, in the preparation method of the present invention, in step 3), Ti3C2T x -The mass ratio of Ag to OKGM is 1:300, and the mass ratio of TA to PF is 1:1.2.
[0025] In another embodiment, the hydrogel for promoting diabetic wound healing obtained by the preparation method of the present invention, in other words, is the use of the hydrogel prepared by the preparation method of the present invention in preparing drugs for promoting diabetic wound healing or in preparing drugs for treating diabetic wounds.
[0026] The hydrogel of the present invention shows promise in treating diabetic wounds due to its high specific surface area, high mechanical strength, photothermal and antibacterial properties. x The large surface area of the membrane provides a large number of active sites for adsorption and controlled release of therapeutic drugs, making it particularly valuable in the long-term management of diabetic wounds where continued treatment is crucial.
[0027] In this study, a new type of KC@PF@TA nanocomposite hydrogel was successfully prepared and its potential application in the repair of diabetic infected wounds was verified. Through synthesis and characterization, the structural and performance advantages of Ti3C2Tx-Ag nanocomposite materials were confirmed, and after combining with KC hydrogel, its photothermal conversion efficiency was significantly improved. In addition, the introduction of Ti3C2Tx-Ag enhanced the antibacterial properties of the hydrogel, while the addition of PF further promoted cell proliferation and migration. The synergistic effect of nanomaterials combined with bioactive molecules in the hydrogel can significantly promote wound healing. The results confirmed that KC@PF@TA hydrogel exhibited excellent antibacterial, cell proliferation and wound healing acceleration capabilities, especially in accelerating inflammatory response inhibition, angiogenesis and tissue remodeling. This shows that KC@PF@TA nanocomposite hydrogel can not only significantly improve the healing speed and quality of diabetic wounds, but also has the potential to become an efficient and safe wound repair material in future clinical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Ti3C2T x-Ag composites, including (A) Ti3AlC2, (B) multilayer Ti3C2Tx, (C) Ti3C2Tx, (D) Ag NPs, (E) Ti3C2Tx x -Ag’s SEM image, (F) Ti3C2Tx-Ag’s TEM image, (G) EDS image of Ti and Ag elements in Figure F.
[0029] Figure 2 Ti3C2T x -Characterization of Ag nanocomposites, the composite materials are Ti3AlC2, multilayer Ti3C2Tx, Ti3C2T x -Ag Among them, (A) XRD spectrum, (B) XPS spectrum, (C) Al 2p, (D) Ti 2p, (E) C1s, and (F) high-resolution XPS spectra of Ag 3d.
[0030] Figure 3 Characterization diagram of KC@TA hydrogel, where (A) is the image of KC@TA hydrogel; (B) is the SEM images of KC and (C) KC@TA hydrogel, (D) is the EDS diagram of Ti and Ag elements of B, (E) FT-IR spectra of OKGM, CMCS and OKGM-CMCS, and (F) XRD spectra of TA and KC@TA.
[0031] Figure 4 The comprehensive performance test results of KC@TA hydrogel, (A) is the formation process of KC@TA hydrogel, (B) is the self-healing process of hydrogel, (C) is the injectability of hydrogel, (D) is the swelling rate of hydrogel, and (E) is the curve of the residual mass ratio of hydrogel over time.
[0032] Figure 5 The results of the in vitro antibacterial performance test of KC@TA hydrogel, where NIR- / NIR+ irradiation (808 nm, 1.2 W / cm 2 , 15min), (A) Staphylococcus aureus and KC, KC@T 200 and KC@TA 200 Colony image after 24h of hydrogel co-culture; (B) Statistical analysis of bacterial survival rate of Staphylococcus aureus; (C) SEM images of Staphylococcus aureus in different groups after near-infrared irradiation.
[0033] Figure 6 The effects of different concentrations of PF on the proliferation and migration of HUVECs in vitro, (A) is the proliferation rate of HUVECs, (B) is the migration rate of HUVECs after PF treatment, and (C) is a representative picture of cell scratches at 0h, 24h and 48h of PF treatment.
[0034] Figure 7The hydrogel of the present invention promotes the healing of diabetic wounds in C57Bl / 6J mice, wherein (A) is a picture of the wounds on days 0, 3, 7, 13 and 21; (B) is a schematic diagram of the change of wound area over time (scale: 20 mm); (C) is a statistical analysis chart of wound area and time; (D) and (E) are HE staining and Masson trichrome staining of wound tissue on day 21, respectively; (F) is a serum ELISA detection chart; and (G) is an ELISA detection chart of TNF-α, IL-6 and VEGF expression levels in tissues. DETAILED DESCRIPTION
[0035] The following examples are representative and are used to further illustrate and understand the essence of the present invention, but are not intended to limit the scope of the present invention.
[0036] Abbreviations and sources:
[0037] Ti3AlC2 powder: aluminum titanium carbide powder, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0038] Ti3C2Tx: Titanium carbide.
[0039] HF: Hydrofluoric acid (40%) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0040] TMAOH: Tetramethylammonium hydroxide (25%) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0041] AgNO3: silver nitrate solution, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0042] OKGM: Oxidized konjac glucomannan was purchased from Shanghai McLean Biochemical Technology Co., Ltd.
[0043] CMCS: Carboxymethyl chitosan was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0044] KC@TA=OKGM / CMCS@Ti3C2Tx-Ag: Ti3C2Tx-Ag hydrogel based on OKGM and CMCS gel matrix.
[0045] PF: Paeoniflorin
[0046] KC@PF@TA hydrogel: OKGM / CMCS@PF@Ti3C2Tx-Ag hydrogel.
[0047] Instruments and equipment used:
[0048] Vacuum freeze drying box (Shanghai Bilang Instrument Manufacturing Co., Ltd.), environmental scanning electron microscope (SEM, Thermo Fisher Scientific, USA), transmission electron microscope (TEM, Thermo Fisher Scientific, USA), X-ray diffraction (XRD, PANalytical, UK) and X-ray photoelectron spectroscopy (XPS, Thermo Fisher Scientific, USA), Fourier transform infrared spectroscopy (FT-IR, Thermo Fisher Scientific, USA).
[0049] The statistical data involved in the following examples are all expressed as mean ± standard deviation (SD). The t test was used for comparison between two groups, the one-way analysis of variance was used for comparison between multiple groups, and the Tukey post hoc test was used for pairwise comparison. GraphPadPrism 9.0 was used for analysis. P<0.05 was considered statistically significant. (*p<0.05, ****p<0.01, p<0.001, ****p<0.0001).
[0050] Example 1 OKGM / CMCS@PF@Ti3C2T x -Ag hydrogel (hereinafter referred to as: KC@PF@TA hydrogel)
[0051] Preparation process:
[0052] 1. Ti3C2T x Nanosheet preparation
[0053] Take 2g Ti3AlC2 powder and slowly add it to 20mL40% HF solution, stir at 550rpm for 24h at room temperature in the dark. Centrifuge the resulting mixture at 3500rpm for 15 minutes. Discard the supernatant and wash the precipitate with 15mL deionized water 5 to 7 times. Wash until the pH of the supernatant is close to neutral. Subsequently, add 20mL 25% TMAOH to the precipitate and stir at 550rpm for 24h in the dark at room temperature. After centrifugation, wash the precipitate again with deionized water until the pH reaches neutral. Resuspend the final precipitate in deionized water and ultrasonically treat for 2h, centrifuge at 3500rpm for 1h. Collect the obtained colloidal solution and vacuum freeze-dry for 24h to obtain ultrathin Ti3C2T x Nanosheet powder.
[0054] 2. Ti3C2T x -Ag nanocomposite preparation
[0055] Take 30mg ultra-thin Ti3C2T x Disperse in 30 mL of deionized water and disperse the solution evenly under ultrasonication for 30 min. Stir the resulting solution at room temperature for 5 min to obtain solution A. Slowly add solution A to 5 mM AgNO3 solution (Ti3C2T xThe mass ratio of Ag to Ag was 1:1, 1:5 or 1:10). After stirring at room temperature for 1 min, the mixture was transferred to a microwave oven. The solution was heated to boiling, and then an appropriate amount of 1% sodium citrate solution was added and heated for another 30 min. After the solution was cooled to room temperature, it was centrifuged at 13000 rpm for 15 min, washed with deionized water for 6 times, and the precipitate was freeze-dried in vacuum for 48 hours to obtain Ti2C2T x -Ag powder.
[0056] 3. Preparation of Nanocomposite Hydrogel
[0057] Oxidized konjac glucomannan (OKGM) and carboxymethyl chitosan (CMCS) were selected as the hydrogel matrix materials. 10 mg Ti3C2T x -Ag powder was ultrasonically dispersed in deionized water to obtain a 1 mg / mL dispersion. CMCS powder was dissolved in deionized water to obtain a 3% CMCS solution, which was solution A. At the same time, OKGM was fully dissolved in deionized water to obtain a 6% solution B. In a polytetrafluoroethylene mold, equal volumes of solutions A and B were added with appropriate amounts of Ti3C2T x -Ag dispersion and paeoniflorin (PF) powder were fully mixed to make Ti3C2T x -The final concentrations of Ag and PF were 200 μg / mL and 500 μM / L, respectively, and KC@PF@TA hydrogel was obtained after standing at room temperature.
[0058] It should be noted that Ti3C2T x Tx in the formula represents the active groups generated on the surface of titanium carbide (Ti3C2), such as -OH, -F, -Cl, etc.
[0059] Comparative Example 1
[0060] Referring to the preparation method of 3 nanometer gel in Example 1, KC@TA hydrogel was prepared.
[0061] Oxidized konjac glucomannan (OKGM) and carboxymethyl chitosan (CMCS) were selected as the hydrogel matrix materials. 10 mg Ti3C2T x -Ag powder was ultrasonically dispersed in deionized water to obtain a 1 mg / mL dispersion. CMCS powder was dissolved in deionized water to obtain a 3% CMCS solution, which was solution A. At the same time, OKGM was fully dissolved in deionized water to obtain a 6% solution B. In a polytetrafluoroethylene mold, equal volumes of solutions A and B were added with appropriate amounts of Ti3C2T x -Ag dispersion is fully mixed to make Ti3C2T x -A final concentration was 200 μg / mL, and the KC@TA hydrogel was obtained by standing at room temperature.
[0062] Comparative Example 2
[0063] Referring to the preparation method of 3 nanometer gel in Example 1, KC@PF hydrogel was prepared.
[0064] Oxidized konjac glucomannan (OKGM) and carboxymethyl chitosan (CMCS) were selected as the hydrogel matrix materials. 10 mg Ti3C2T x -Ag powder was ultrasonically dispersed in deionized water to obtain a 1 mg / mL dispersion. CMCS powder was dissolved in deionized water to obtain a 3% CMCS solution A. At the same time, OKGM was fully dissolved in deionized water to obtain a 6% solution B. Paeoniflorin (PF) powder was added to equal volumes of solution A and B in a polytetrafluoroethylene mold and mixed thoroughly to a final concentration of PF of 500 μM / L. The mixture was allowed to stand at room temperature to obtain KC@PF hydrogel.
[0065] 4. Physicochemical characterization of nanomaterials and hydrogels
[0066] Test instruments used:
[0067] Environmental scanning electron microscope (SEM, Quattro S, ThermoFisher Scientific, DE, USA),
[0068] Transmission electron microscopy (TEM, Talos F200S, ThermoFisher Scientific, DE, USA),
[0069] X-ray diffraction (XRD, PANalytical X'pert Powder, LON, UK),
[0070] X-ray photoelectron spectroscopy (XPS, ESCALAB250Xi, ThermoFisher Scientific, DE, USA) and Fourier transform infrared spectroscopy (FT-IR, Nicolet iS50, ThermoFisher Scientific, DE, USA) were used to characterize the morphology and physicochemical properties of all samples.
[0071] 4.1Ti3C2T x Characterization of Ag-nanocomposites
[0072] Ti3C2T x -The preparation process of Ag nanocomposites is as follows Figure 1 As shown. The compact structure of Ti3AlC2 ( Figure 1 A) After HF etching of the Al layer, a multilayer, hollow accordion structure of multilayer Ti3C2Tx ( Figure 1 B). After TMAOH intercalation and ultrasonic exfoliation, ultrathin Ti3C2T x Nanosheets, the size is about 300nm ( Figure 1 C).
[0073] When Ti3C2T x When the mass ratio of Ag to Ti3C2T is 1:10, the Ag loading reaches the supersaturation level, so Ti3C2T x The subsequent experiments were carried out with a mass ratio of 1:5 to Ag. x There are a large number of active -OH groups on the surface, which causes the Ag NPs with uniform particle size originally reduced by sodium citrate to become uneven in size ( Figure 1 DF). And elemental analysis further confirmed that AgNPs were successfully loaded on Ti3C2Tx nanosheets ( Figure 1 G).
[0074] XRD test spectrum (such as Figure 2 ) The results show that after HF etching, the peak at (104) of the Ti3AlC2 raw material completely disappears, reflecting that the structure of the crystal plane is destroyed, that is, the Al layer is etched away; while the intensity of the (004) peak decreases and the shift and intensity of the (002) peak decrease, indicating that the interlayer spacing of Ti3C2Tx has changed and the orderliness of the layered structure has decreased. After the surface of the Ti3C2Tx nanosheets is loaded with silver nanoparticles, obvious peaks of the (111), (200), and (220) crystal planes are observed in the XRD spectrum, corresponding to the characteristic peaks of Ag, indicating that the silver nanoparticles are successfully loaded on the surface of the Ti3C2Tx nanosheets and their crystal structure has good crystallinity ( Figure 2 A). These results comprehensively demonstrate the structural evolution of Ti3AlC2 in different processing steps and the successful introduction of silver nanoparticles. The XPS spectrum shows that after the Al layer is removed, new peaks (such as C1s 283.3eV, 280eV) indicate that the bonding between C and Ti has changed, and the Ti2p peak shifts to the left, indicating a change in the chemical environment of Ti, possibly forming a surface termination group (such as Tx = -OH, -F, -Cl). The binding energy of the Ag3d 367.3eV, 373.4eV peaks is slightly lower than that of pure silver, suggesting that some kind of surface chemical bond may be formed due to its interaction with Ti3C2Tx. And the Ti2p peak shifts to the right, further supporting this interaction ( Figure 2 BF).
[0075] 4.2 Structural characterization and analysis of KC@TA hydrogel and its comprehensive properties
[0076] The KC (OKGM / CMCS) hydrogel synthesized according to the preparation has a clear three-dimensional void structure ( Figure 3 A). It can be clearly seen that the pores of the hydrogel are reduced and the three-dimensional structure of the hydrogel becomes more compact after the introduction of TA (Ti3C2Tx-Ag) nanocomposite materials ( Figure 3 B). Elemental analysis further confirmed that TA was introduced into the hydrogel and KC@TA hydrogel was successfully constructed ( Figure 3 C). By analyzing the bonding reaction between KC hydrogel synthesis, the FTIR spectrum shows that OH and NH bonds (3421cm -1 ) position slightly changed, which may be due to the change of hydrogen bonds caused by cross-linking. -1 ) may indicate the formation of new amide bonds or carboxyl groups. This indicates that CMCS and OKGM successfully formed a cross-linked three-dimensional network structure, which retained their respective main chemical characteristics and formed new cross-linked bonds ( Figure 4 D). After the introduction of TA, a corresponding peak appeared on the (111) crystal plane, confirming that TA was successfully loaded into the KC hydrogel, and the KC@TA hydrogel was dark green ( Figure 3 EF).
[0077] Comprehensive performance:
[0078] (1) Self-healing and injectability: One hydrogel was cut into two pieces. The pieces were left to stand at room temperature for 10 minutes to observe the self-healing ability. In addition, the hydrogel solution was loaded into a 1 mL syringe and gently pushed to evaluate its injectability.
[0079] (2) Swelling: The dried KC@TA hydrogel was immersed in 500 mL of deionized water at room temperature. At specific times (0, 1, 2, 3, 4, 5, 6, 7, 8, 12, and 24 h), the hydrogel was taken out and the excess surface water was gently absorbed using dry filter paper. The weight of the hydrogel at each time point was recorded. The swelling ratio was calculated using the following formula:
[0080] Swelling rate % = (W t -W0) / W0×100% (1-1)
[0081] Among them, W0, W t are the initial mass of the hydrogel and the mass at different times, respectively.
[0082] (3) Degradation: Weigh the hydrogel that has reached swelling equilibrium to obtain the initial mass W i Then soak in 100 mL of physiological saline (0.9% NaCl). Take out the hydrogel every day (12 days in total), dry it with absorbent paper, and weigh it as W. fThe remaining weight percentage of the hydrogel was calculated using the following equation:
[0083] Remaining weight % = W f / W i ×100%(1-2)
[0084] Where W i , W f are the initial mass of the hydrogel and the mass at each time point, respectively.
[0085] CMCS, OKGM and Ti3C2T x -Ag mixture can undergo a rapid cross-linking reaction to form a hydrogel within 2 minutes ( Figure 4 A). The hydrogel has good self-healing properties. If the hydrogel divided into two parts is placed at room temperature, it can heal into a complete hydrogel in 5 minutes ( Figure 4 B). The hydrogel also exhibits excellent injectability, which can meet the treatment requirements for irregular wounds ( Figure 4 C). Studies have shown that KC@TA hydrogel can swell rapidly within 1 hour, and the swelling rate gradually increases until 12 hours, and the swelling equilibrium is almost reached between 12 hours and 24 hours ( Figure 4 D). At the same time, its degradation rate is slow, and it takes about 11 days to completely degrade ( Figure 4 E). The above results show that KC@TA hydrogel has high water absorption capacity and slow degradation rate, suggesting that it helps to form a moist environment conducive to healing at the wound site, provides long-term drug release to reduce the frequency of dressing changes and improve the therapeutic effect.
[0086] Example 2 In vitro antibacterial experiment
[0087] The in vitro antibacterial activity of the hydrogel against Staphylococcus aureus (ATCC 25923) was observed by plate colony counting and scanning electron microscopy. 200 、KC@TA 25 / 50 / 100 / 200 The hydrogels were sterilized by soaking in 75% ethanol for 2 h. After sterilization, they were rinsed three times with sterile PBS to remove the residual ethanol and then placed in a 24-well plate. 6 CFU / mL bacterial suspension was injected onto the surface of each hydrogel sample. The bacteria were incubated on the hydrogel surface for 15 min and a power density of 1.2 W / cm 2 808nm near-infrared laser irradiation. After treatment, add 990μL sterile PBS to each well to resuspend the surviving bacteria. Take 10μL of the resuspended bacterial solution and spread it on the agar plate. After incubation in a 37℃ constant temperature incubator for 18-24h, count the number of colonies. The bacterial survival rate was calculated by comparing the number of colonies in each experimental group with that in the control group, and the colony count that was not exposed to near-infrared irradiation was used as the reference value.
[0088] The remaining bacterial suspension was centrifuged at 3000 rpm for 5 min, the supernatant was discarded, and the bacteria were fixed and dehydrated as follows. (1) Fixation: Add 1 mL of sterile PBS to the bacterial pellet, gently blow to mix, centrifuge at 3000 rpm for 5 min, and repeat three times. After washing, slowly add 1 mL of 4% glutaraldehyde to the pellet, mix thoroughly, and incubate at 4°C for 4 h to fix the bacteria. Then centrifuge the suspension at 3000 rpm for 5 min, discard the supernatant, wash three times with 1 mL of PBS, and collect the pellet. Next, add 2.5% glutaraldehyde, and let the mixture stand at 4°C for 1 h. Wash three times with 1 mL of PBS. (2) Dehydration: Add 1 mL of 20% (w / v) ethanol to the pellet, mix gently, let stand for 10 min, centrifuge and discard the supernatant. Subsequently, use 1 mL of 50%, 80% and 100% (w / v) ethanol to dehydrate continuously for 10 min, centrifuge and discard the supernatant. Finally, gently shake to remove the remaining ethanol. Then use a toothpick to transfer a small amount of the dehydrated bacterial sample to the conductive adhesive. The sample surface was gold-plated, and the bacterial morphology was observed using a scanning electron microscope.
[0089] Experimental results:
[0090] In near infrared (808nm, 1.2W / cm 2 ) irradiated (NIR+) and not irradiated (NIR-), KC, KC@T 200 and KC@TA 200 The antibacterial effect of hydrogel on Staphylococcus aureus. The study found the bacterial colony formation of different samples on agar plates under NIR- and NIR+ conditions. Under NIR-, KC@T 200 The colony count of the groups decreased slightly, and the colony count of KC@TA treatment was the least. However, under NIR+, no bacterial colonies grew in the KC@TA group, and statistical analysis showed that the activity of bacteria was reduced to about 10%, which was significantly lower than that of the other two groups. This indicates that Ti3C2T x -Ag modified hydrogel has better photothermal antibacterial activity ( Figure 5 A, B). In addition, the SEM images of Staphylococcus aureus showed that after NIR irradiation, the bacteria in the KC group maintained a smooth spherical morphology. In contrast, the KC@T 200 The treated bacteria showed partial deformation, while KC@TA 200 The treated bacteria were significantly smaller and showed more severe deformation, which further confirmed the enhanced antibacterial effect ( Figure 5 C).
[0091] Example 3 In vitro cell experiment
[0092] ① Cell proliferation: Human umbilical vein endothelial cells (HUVECs) were cultured at 5×10 3Each well was inoculated with 100uL of paeoniflorin. After 24h, paeoniflorin was treated. The final concentrations of paeoniflorin were 3.125, 6.25, 12.5, 25, 50, 100, and 200μM, respectively. Six replicate wells were set for each concentration. After 24, 48, and 72h of continuous culture, the 96-well plate was taken out, the culture medium was discarded, and basic culture medium containing 10% CCK-8 solution was added to each well. The cells were placed in an incubator at 37°C and 5% CO2 by volume for 1h. The cell proliferation rate was calculated according to the following formula:
[0093] Cell proliferation rate % = [(OD 实 -OD 空 ) / (OD 阴 -OD 空 )]×100%(1-3)
[0094] OD 实 OD 阴 and OD 空 They are the absorbance values at 450nm of the experimental group, negative control group and blank group respectively.
[0095] ② Cell scratch: 1×10 6 The cells were inoculated into 6-well plates with 2 mL per well. The cells covered the bottom of the wells. A 200 μL pipette tip was used to scratch the bottom of the well plate vertically. The cells were washed 3 times with PBS and divided into a control group and a paeoniflorin group (5, 10, 20 uM). The cells were placed in an incubator and cultured for 24 h and 48 h, then taken out and washed 3 times with PBS. The migrated cells of each group were photographed with an inverted microscope, and the average value was calculated. The control group was set as 100%.
[0096] Although KC@TA hydrogel alone has excellent photothermal antibacterial properties, wound repair requires not only antibacterial properties but also the promotion of cell proliferation, migration, and tissue regeneration. To this end, the effects of different concentrations of PF on cell proliferation and migration were further explored.
[0097] The experimental results showed that after PF was used to treat human umbilical vein endothelial cells in the concentration range of 3.125-200 μM for 48 hours, the cell proliferation activity increased with the increase of PF concentration, and it was significantly enhanced from 12.5 μM and reached a peak at 200 μM, indicating that the promoting effect of PF on cell proliferation was dose-dependent ( Figure 6 A). Because low concentration (6.25μM), medium concentration (12.5μM), and high concentration (25μM) of PF were selected to treat cells, the migration rate at 0h, 24h, and 48h was observed and calculated. The results showed that the migration ability of cells increased significantly over time, especially at 48h, and the cell migration ability of 25μM PF was the highest ( Figure 6B, C). This indicates that PF can not only promote cell proliferation, but also accelerate cell migration, which is essential for wound healing. Therefore, the cell proliferation-promoting function of paeoniflorin and the photothermal antibacterial properties of KC@TA were integrated to prepare KC@PF@TA hydrogel for subsequent experimental studies.
[0098] Example 4 In vivo diabetic infection wound healing experiment
[0099] 5-week-old C57BL / 6J male mice were selected and fed with a high-fat diet (60% kcal) after 1 week of adaptive feeding. After 4 weeks of high-fat diet, STZ mice were intraperitoneally injected with streptozotocin (pH=4.2-4.5 citric acid buffer) 30 mg / kg. Before intraperitoneal injection, the mice fasted for 12 hours overnight, and the injections were continued for 5 days, and eating was resumed 2 hours after each injection. After 3-5 days, the random blood glucose of the mice was measured and recorded. The type 2 diabetes model was successfully established in mice with a blood glucose level of >16.7mM.
[0100] The mice were anesthetized with an anesthesia machine and the back was shaved. The full-thickness skin with a diameter of 6 mm was cut, the silicone gasket was sutured and fixed, and 20 μL of bacterial solution (10 8 CFU / mL) to establish an infectious full-thickness wound model. The wound was treated with KC, KC@PF, and KC@PF@TA hydrogels at 1.2W / cm 2 808nm near-infrared irradiation for 3 minutes, and an infrared thermal imager was used to monitor the temperature of the wound before and after irradiation. The dressing was changed every 2 days. The wound was photographed on days -2, 0, 3, 7, 13, and 21 to observe the wound healing. Image J software was used for statistical analysis, and the wound healing rate was calculated according to the following formula:
[0101] Wound area % = A t / A0×100%(1-3)
[0102] Among them A t A0 and A1 are the wound areas at different time points and -2 days respectively.
[0103] In vitro studies have shown that KC@PF@TA hydrogel has great application prospects in diabetic wound repair. Therefore, by giving streptozotocin (STZ) to C57BL / 6J mice daily for 5 consecutive days and detecting blood sugar changes, a diabetic mouse model was successfully established when the blood sugar level was stable >16.7mM. Then, a 6mm full-thickness wound was created on the back and infected with Staphylococcus aureus for 48 hours, and the wound was treated with KC, KC@PF and KC@PF@TA hydrogels respectively. Figure 7As shown in A and B, the wound healing speed of KC@PF and KC@PF@TA hydrogels was significantly faster than that of the blank hydrogel KC group. It is worth noting that the wound healing rate of the KC@PF group was about 70.7% on the 21st day, while the wound healing rate of the KC@PF@TA hydrogel was as high as 88.12%, which can significantly accelerate the wound healing speed (****p<0.0001)( Figure 7 C). The results showed that compared with blank hydrogel, the drug-loaded hydrogel can effectively shorten the inflammatory phase and allow the wound to enter the proliferation phase of healing. More importantly, the KC@PF@TA hydrogel can further accelerate the tissue remodeling phase. On the 21st day, the KC group still had some scabs and an incomplete epidermal structure. The KC@PF group had a clear and relatively complete epidermal layer, but the epidermal layer was thicker, and the collagen fibers were uneven and arranged in a disorderly manner. However, the wound treated with KA@PF@TA hydrogel showed a complete epidermal layer similar to that of normal skin, and the new collagen volume was higher, and the collagen fibers were uniform and arranged in an orderly manner ( Figure 7 D, E). This shows that the wound treated with KC@PF@TA hydrogel was more similar to healthy skin at 21 days, with good healing and accelerated remodeling. In diabetic wounds, excessive inflammatory response and angiogenesis disorders are important reasons for the prolonged wound healing process. Figure 7 As shown in F and G, the expression levels of inflammatory factors IL-6 and TNF-α in the KC@PF and KC@PF@TA hydrogel treatment groups were significantly reduced, and the expression of VEGF was significantly increased, and the VEGF expression level in the KC@PF@TA group was the highest, indicating that KC@PF@TA hydrogel can inhibit inflammatory response and promote angiogenesis and tissue regeneration.
[0104] In summary, the above experimental results show that the hydrogels of TA and PF have a significant synergistic effect in the treatment of diabetic wounds and significantly improve the therapeutic effect of diabetic skin ulcers.
Claims
1. A hydrogel for promoting diabetic wound healing, comprising Ti3C2T x -Ag, paeoniflorin (PF) and a gel matrix, wherein the gel matrix is an oxidized konjac glucomannan (OKGM) solution and carboxymethyl chitosan (CMCS).
2. The hydrogel according to claim 1, prepared by the following method, which comprises: 1) Ti3C2T x The powder was dispersed in deionized water, added to AgNO3 solution, stirred, heated to boiling, and an appropriate amount of sodium citrate solution was added. After the reaction was completed, the precipitate was separated to obtain Ti3C2T x -Ag(TA) powder; 2) Ti3C2T x -Ag(TA) powder was dispersed in deionized water to form a dispersion and paeoniflorin (PF) was mixed with oxidized konjac glucomannan (OKGM) solution and carboxymethyl chitosan (CMCS) solution to prepare KC@PF@TA hydrogel.
3. The hydrogel according to claim 1, wherein in step 2), the mass ratio of TA to PF is 1:(1-1.2).
4. The hydrogel according to claim 1, wherein in step 2), Ti3C2T x The mass ratio to Ag is 1:(1-10), preferably 1:
5.
5. A method for preparing a hydrogel for promoting diabetic wound healing, comprising the following steps: 1) Ti3AlC2 powder was added to 40% HF solution, stirred and reacted at room temperature in the dark, the obtained reaction mixture was centrifuged, the supernatant was discarded, and the precipitate was washed with deionized water until the pH of the supernatant was close to neutral. The precipitate was mixed with 25% TMAOH, stirred and reacted at room temperature in the dark, centrifuged after the reaction, and the precipitate was washed with deionized water until the pH reached neutral. The precipitate was resuspended in deionized water and ultrasonically treated, the colloidal solution was separated, and vacuum freeze-dried to obtain Ti3C2T x Nanosheet powder; 2) Ti3C2T x The mixture was dispersed in deionized water to form a uniform dispersed solution, added to the AgNO3 solution, stirred and mixed, heated to boiling, and then an appropriate amount of 1% sodium citrate solution was added to react. After the reaction was completed, the mixture was cooled to room temperature, the precipitate was separated, washed with deionized water, and the precipitate was vacuum freeze-dried to obtain Ti3C2T x -Ag nanocomposite powder; 3) Ti3C2T x -Ag powder was ultrasonically dispersed in deionized water to form a dispersion, and paeoniflorin (PF) was added and mixed with oxidized konjac glucomannan (OKGM) solution and carboxymethyl chitosan (CMCS) solution to prepare KC@PF@TA hydrogel.
6. The preparation method according to claim 5: in step 1), the mass volume ratio of Ti3AlC2 to TMAOH is 1gTi3AlC2:10mL TMAOH.
7. The preparation method according to claim 5: in step 2), Ti3C2T x The mass ratio to Ag is 1:(1-10), preferably 1:
5.
8. The preparation method according to claim 5, wherein in step 3), the mass ratio of OKGM to CMCS is 2:
1.
9. The preparation method according to claim 5, in step 3), the dispersed solution contains Ti3C2T x -Ag concentration 1mg / mL.
10. The preparation method according to claim 5, wherein in step 3), Ti3C2T x -The mass ratio of Ag to OKGM is 1:300.
Citation Information
Cited By
Conductive electrospinning dressing with photo-thermal antibacterial function as well as preparation method and application of conductive electrospinning dressing
CN119838042A
Antibacterial heterojunction nano-material for repairing wound infected by diabetes mellitus as well as preparation method and application of antibacterial heterojunction nano-material
CN122075777A
An antibacterial heterojunction nanomaterial for repairing diabetic infected wounds and a preparation method and application thereof
CN122075777B